Brazilian Atlantic rainforest endangered biodiversity: a new species of the Dichotomius sericeus (Harold, 1867) species group (Coleoptera: Scarabaeidae: Scarabaeinae) - Silva, Fernando A.b.; Moura, Ana Beatriz Gomes; Araújo, Josival Francisco; de Moura, Rita De Cassia (Zootaxa, 2020)
Dichotomius valoisae new species (Coleoptera: Scarabaeidae: Scarabaeinae: Dichotomiini) from Santa Luzia do Itanhi, Sergipe, Brazil, is described based on external differences from its congeners. Diagnostic characters and a brief discussion about its conservation status are provided, as well as an updated identification key to the Dichotomius sericeus (Harold) species group.